STUDY ON THE PERCEPTION OF STUDENTS OF THE FACULTY OF MANAGEMENT AND RURAL DEVELOPMENT REGARDING THE TEACHING - LEARNING-ASSESSMENT ACTIVITY CARRIED OUT ONLINE DURING THE COVID-19 PERIOD - Ramona Elena ANGHEL; Alina MARCUTA; Cristiana TINDECHE; Mihaela ROSU; Constantin TRAISTARU; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The role of a higher education institution is to train specialists who have the necessary skills for their integration into the labor market. The Faculty of Management and Rural Development is one of the 7 faculties of the University of Agronomic Sciences and Veterinary Medicine in Bucharest and which, through the mission and objective, it has proposed as the university curriculum to increase the quality of the didactic act with the aim of training specialists who can integrate into the current knowledge-based society, specialists who can assume responsibilities, be creative, original, flexible, adaptable, with an analytical thinking, innovative and able to run businesses, so that the motto of the faculty is "Preparing to lead!". The new challenges facing today's society make higher education institutions rethink their priorities, having to continuously adapt to meet the challenges that accompany modern society. Therefore, they need modern teaching-learning-evaluation strategies, which respond to the changing requirements and require a digital transformation. The experience gained during the Covid-19 pandemic has accelerated progress in this direction, but more is needed so that the needs of young people raised in a digital society, with digital needs and digital skills can be met. The present study aims to measure the perception of the Faculty of Management and Rural Development students regarding the extent to which digital technology has been applied in the online teaching-learning-evaluation process and its effectiveness. The research methodology assumed the analysis of specialized literature regarding the use of digitization in the application of modern methods in the teaching-learning-evaluation process. The case study was carried out starting with a questionnaire that contained 15 questions addressed to the students of the Faculty of Management and Rural Development. The processing of the answers was carried out with the help of statistical methods, and the results obtained after their interpretation showed that both the teaching staff and the students adapted quite quickly to the online education system. The teaching-learning methods were varied, as were the learning tools used. Among the strong points of online education were flexibility, accessibility, and a variety of methods used in the teaching-learning activity, and among the weak points were identified: maintaining the students' attention during the teaching-learning activity, time management, or the level of digital skills of the teaching staff.